2018
DOI: 10.1002/rmv.1995
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the impact of point‐of‐care testing for influenza on the outcomes of patients with acute respiratory tract infection

Abstract: Acute respiratory tract infections are a major cause of morbidity and mortality and represent a significant burden on the health care system. Laboratory testing is required to definitively distinguish infecting influenza virus from other pathogens, resulting in prolonged emergency department (ED) visits and unnecessary antibiotic use. Recently available rapid point-of-care tests (POCT) may allow for appropriate use of antiviral and antibiotic treatments and decrease patient lengths of stay. We undertook a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
82
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 53 publications
2
82
1
1
Order By: Relevance
“…Continuation of antibiotics after confirmation of the viral aetiology is not unique to COVID-19 [26,27]. Moreover, randomized controlled studies have not shown a consistent effect of point-of-care testing for influenza on antibiotic prescription rates [28]. Uncertainty avoidance, in this case fear of the possibility of a concurrent or a developing bacterial co-infection, might be too compelling and lead to antibiotic prescription as a coping strategy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Continuation of antibiotics after confirmation of the viral aetiology is not unique to COVID-19 [26,27]. Moreover, randomized controlled studies have not shown a consistent effect of point-of-care testing for influenza on antibiotic prescription rates [28]. Uncertainty avoidance, in this case fear of the possibility of a concurrent or a developing bacterial co-infection, might be too compelling and lead to antibiotic prescription as a coping strategy [27].…”
Section: Discussionmentioning
confidence: 99%
“…might improve the impact on clinical outcomes as results are available before any initial treatment or management is established by the treating physician. To our knowledge, this is the first review to specifically assess the clinical impact of rapid molecular tests, and not rapid antigen tests, without a restriction in the detection of influenza virus and RSV [45,46]. The included studies, even the high-quality randomized studies [1,20,21,24,25], show heterogeneous results.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with data published by other groups, like Tillekeratne et al ( 17 ), who showed a 20% decrease in the antibiotic prescription with the use of an POCT for influenza confirmation, and Jennings et al ( 18 ), who showed a five-fold increase of antibiotic prescriptions in clinical diagnosed patients. Egilmezer et al ( 19 ) recently published a systematic review of the impact of diagnosing influenza with a POCT in patients with acute respiratory tract infection. The main findings were that a positive POCT significantly increased the proper use of antivirals and decreased antibiotic prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…The main findings were that a positive POCT significantly increased the proper use of antivirals and decreased antibiotic prescriptions. Unfortunately, the number of papers addressing prospectively the impact of influenza POCTs on antibiotic treatment in pediatric primary care were only two out of the 30 papers included in this systematic review ( 19 ). These papers confirm that decision-making process of an antibiotic prescription is vastly influenced by an accurate diagnosis ( 17 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation